5(4x-6)-8=6x-24

Simple and best practice solution for 5(4x-6)-8=6x-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4x-6)-8=6x-24 equation:


Simplifying
5(4x + -6) + -8 = 6x + -24

Reorder the terms:
5(-6 + 4x) + -8 = 6x + -24
(-6 * 5 + 4x * 5) + -8 = 6x + -24
(-30 + 20x) + -8 = 6x + -24

Reorder the terms:
-30 + -8 + 20x = 6x + -24

Combine like terms: -30 + -8 = -38
-38 + 20x = 6x + -24

Reorder the terms:
-38 + 20x = -24 + 6x

Solving
-38 + 20x = -24 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-38 + 20x + -6x = -24 + 6x + -6x

Combine like terms: 20x + -6x = 14x
-38 + 14x = -24 + 6x + -6x

Combine like terms: 6x + -6x = 0
-38 + 14x = -24 + 0
-38 + 14x = -24

Add '38' to each side of the equation.
-38 + 38 + 14x = -24 + 38

Combine like terms: -38 + 38 = 0
0 + 14x = -24 + 38
14x = -24 + 38

Combine like terms: -24 + 38 = 14
14x = 14

Divide each side by '14'.
x = 1

Simplifying
x = 1

See similar equations:

| 2x^2+9*x-7=0 | | x-22=4 | | x+5+133+x= | | x^3+4x^2+5x+2=0 | | 3(5a-2)-2a+10= | | 3(n-1.8)=2n+1 | | 6(x-1)-2(2-x)=8-(2-6x) | | x^4+4x^3+5x^2+2x=0 | | q*(5-q)= | | 3y=-28-x | | 2(1+x)-1=3(2x+1)+2 | | z-48=-32 | | (5-q)-5q= | | 8x-1/5-1=(50-2x/9)+(3x+3/4) | | 16x+7x+15=0 | | 5-q= | | 10n=4 | | 5x-4=14x-13 | | 3x+26=10x-41 | | 20*(4x+1)-24(3x+1)=15*60-60*(25-x) | | 15x-176=6x-14 | | 24*(3x-1)-20*(5x+1)=120*(x+1)-3*120 | | 6y+(8)(7)-4=42 | | 11x+2=2x+128 | | 155-5x=40x+15x | | 7-10x=55-24x | | x^2+16x+9=18 | | 145-8x=8x+15 | | 182-6x=5x+24 | | 2x+96=9x-9 | | 81-5x=22x+21 | | 8-8x=68-36x |

Equations solver categories